2022
DOI: 10.3390/vetsci9070329
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Behavior between Normal and Atopic Keratinocytes in Culture: Pilot Studies

Abstract: Skin barrier dysfunction is important in atopic dermatitis and can be secondary to inflammation. Observation of keratinocytes in culture may show intrinsic differences. TransEpithelial Electrical Resistance (TEER) measures epithelial permeability. We cultured normal and atopic keratinocytes and found that TEER of atopic keratinocytes was significantly lower (p < 0.0001) than that of normals. Atopic keratinocytes grew upwards, first creating isolated dome-like structures and later horizontally into a monolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Along with filaggrins and NMFs, other structural proteins that have been studied in atopic dogs and humans include the tight junction proteins claudin-1 and occludin. [22][23][24][25] Both proteins have been shown to be significantly decreased in the skin of atopic dogs when compared to healthy canine skin, further highlighting the impaired skin barrier in dogs with AD. Recently, 22 using an experimental model of acute canine AD, authors have shown a decrease in protein expression and distribution of corneodesmosin, another structural protein present in the SC, in atopic skin when compared to healthy skin.…”
Section: Updates On Stratum Corneum Structural Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with filaggrins and NMFs, other structural proteins that have been studied in atopic dogs and humans include the tight junction proteins claudin-1 and occludin. [22][23][24][25] Both proteins have been shown to be significantly decreased in the skin of atopic dogs when compared to healthy canine skin, further highlighting the impaired skin barrier in dogs with AD. Recently, 22 using an experimental model of acute canine AD, authors have shown a decrease in protein expression and distribution of corneodesmosin, another structural protein present in the SC, in atopic skin when compared to healthy skin.…”
Section: Updates On Stratum Corneum Structural Proteinsmentioning
confidence: 99%
“…Along with filaggrins and NMFs, other structural proteins that have been studied in atopic dogs and humans include the tight junction proteins claudin‐1 and occludin 22–25 . Both proteins have been shown to be significantly decreased in the skin of atopic dogs when compared to healthy canine skin, further highlighting the impaired skin barrier in dogs with AD.…”
Section: Updates On Stratum Corneum Structural Proteinsmentioning
confidence: 99%
“…No study so far has concurrently investigated the antibodies produced against filaggrin and filaggrin 2 in the same set of skin biopsies. One recently published study from our group has reported on the immunofluorescent staining of both filaggrin and filaggrin 2 on primary cell cultures of keratinocytes [19]. This study showed some overlapping features but also some differences in the staining between filaggrin and filaggrin 2.…”
Section: Introductionmentioning
confidence: 55%
“…The 15 kD band was also present in baseline biopsy samples, so it was an atopic feature and not the result of allergen exposure. Interestingly, when our group worked on the Western blots of filaggrin from cell cultures of atopic keratinocytes [19], this band was not detected. Thus, it is theorized that the additional degradation of filaggrin that occurs in skin biopsies of atopic dogs, and not in atopic keratinocytes grown in culture, may be the result of the cytokine milieu present in atopic skin biopsies and not an intrinsic feature of atopic keratinocytes.…”
Section: Discussionmentioning
confidence: 93%
“…Epidermal barrier dysfunction plays a key role in the pathogenesis of CAD, as it allows microbial adherence, penetration of allergenic proteins, and may trigger inflammatory and allergic responses. That is why one of the targets of topical therapy in CAD patients is to restore epidermal barrier integrity and function [ 1 , 3 , 8 , 9 , 10 , 11 , 12 ]. Currently, the management of the atopic canine patient includes restoration of the skin barrier function by, for instance, applying sphingolipids and fatty acid emulsions [ 2 , 13 ].…”
Section: Introductionmentioning
confidence: 99%